2016
DOI: 10.1111/ajt.13581
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Using CD45RA and CD28 to Investigate CD8 Subsets in Kidney Transplant Recipients

Abstract: The deleterious role of CD8 T cells in kidney graft outcome has regained interest over the years, and memory T cells are considered as one of the main hurdles to achieve transplantation success. Monitoring the CD8 immune response in transplant recipients involved a heterogeneous combination of markers, but the justification of their choice is rarely stated. Whereas the number of parameters is not an issue in phenotypic analysis, functional assays have to accommodate the cell number with the narrowing of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
(66 reference statements)
2
13
0
Order By: Relevance
“…For a more granular analysis of the heterogeneous and functionally distinct memory and effector populations within CD3 + T cell compartment, we included additional conventional memory markers CD45RA and CCR7 (19, 2527). Utilizing a gating strategy involving these four memory markers (Supplemental Figure 6) revealed belatacept resistant rejection was highly associated with elevated pre-transplant frequencies of CD28 + CD95 + CD45RA + CCR7 − CD8 T cells, so-called CD28 + CD8 + T EMRA (Figure 4c–d, P<0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a more granular analysis of the heterogeneous and functionally distinct memory and effector populations within CD3 + T cell compartment, we included additional conventional memory markers CD45RA and CCR7 (19, 2527). Utilizing a gating strategy involving these four memory markers (Supplemental Figure 6) revealed belatacept resistant rejection was highly associated with elevated pre-transplant frequencies of CD28 + CD95 + CD45RA + CCR7 − CD8 T cells, so-called CD28 + CD8 + T EMRA (Figure 4c–d, P<0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The use of CD28 and CD95 is a standard approach for identifying na€ ıve (CD28 + CD95 À ), central memory (CD28 + CD95 + ), and effector/effector memory (CD28 À CD95 + ) T cells when phenotyping subsets in primates (21,22,25). For a more granular analysis of the heterogeneous and functionally distinct memory and effector populations within CD3 + T cell compartment, we included additional conventional memory markers CD45RA and CCR7 (19,(25)(26)(27). Utilizing a gating strategy involving these four memory markers ( Figure S6) revealed that belatacept-resistant rejection was highly associated with elevated pretransplant frequencies of CD28 + CD95 + CD45RA + CCR7 À CD8 T cells, so-called CD28 + CD8 + T EMRA ( Figure 4C Belatacept-and tacrolimus-based immunosuppression gave rise to two distinct study populations: those animals that were "susceptible" to therapy (gray lines) and those that were "resistant" to treatment (black lines).…”
Section: Elevated Frequency Of Cd28 + Cd8 + T Emra Is Associated Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the low expression of costimulatory molecules CD28 and CD27 by TEMRA CD8 T cells (25), we hypothesize that the effector functions of TEMRA CD8 T cells are triggered by pro-inflammatory cytokines such as IL-15, which are expressed and transpresented by conventional dendritic cells and macrophages (26, 27). Of note, CD45RA and CD28 markers were used to identify NAÏVE (CD45RA + CD28 + ), EM (CD45RA − CD28 + ), and TEMRA (CD45RA + CD28 − ) CD8 subsets (Figure S1 in Supplementary Material) (25). Stimulation with plate-bound anti-CD3 and IL-15 results in the upregulation of the activation marker CD25 and early proliferation marker CD69 by TEMRA CD8 from KT recipients (mean ± SEM 79.0 ± 5.4 and 67.8 ± 4.6%, respectively; p  < 0.0001 vs. no stimulation; Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…IL-15 favors the migration of memory CD8 T cells toward inflamed tissues (11) and supports the proliferation and the survival of CCR7 − memory CD8 T cell pool (30). The CCR7 − memory CD8 include EM and TEMRA with a heterogeneous frequency across HV and in patients with strong immune stimulation such as kidney transplantation (25). By investigating the reactivity of TEMRA and EM CD8 and by characterizing their metabolic profiles, we aimed to assess whether TEMRA and EM CD8 respond in similar manner to IL-15 stimulation.…”
Section: Discussionmentioning
confidence: 99%